(untitled) (Journal of the Spanish Institute for Strategic Studies, 2024)
It is a defense problem the fact that we have no defined operational environment regarding cognitive domain, and we need to tackle it. Although it is true that psychological operations are difficult to prevent, and its real impact is still uncertain, it is necessary to study their origin and way, in search of delimiting actions that are considered harmful. This is further complicated in a conflict situation, due to the emotional burden that it entails, and the high interests involved on both sides. For this reason, this report proposes a prototype for the detection of manipulation and propaganda towards civilians in psychological operations within a conflictive context. On the one hand, this is intended to identify language patterns that could potentially modify the perception of the individual (increasing the conflict or polarization of those involved), and second, to preserve the protection of the rights and freedoms of citizens. Understanding the expansion and fast dissemination of information today, it is also proposed to train a language AI to detect indicators that suggest manipulation of information, regardless of its content. Once adapted, this prototype would be used by the State Defense as a reliable tool. The main aim is to analyze the information based on the cognitive impact that it may have on the individual unconsciously, and make it processing conscious and active.